Optical Properties of ZnO Nanoparticles Prepared by Chemical Method Using Poly(vinyl pyrrolidone) as Capping Agent - Jesuvathy Sornalatha1, D.; Murugakoothan2, P. (Asian Journal of Chemistry, 2013)
Zinc oxide nanoparticles are synthesized by chemical method using poly(vinyl pyrrolidone) as capping agent. ZnO nanoparticles are characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, Fourier transform infrared spectroscopy, photoluminescence and UV-visible diffuse reflectance/absorption spectroscopy. The XRD pattern of ZnO nanoparticles suggests that the synthesized ZnO nanocrystallites have hexagonal wurtzite structure. SEM and TEM images reveal the shape and size of the ZnO nanoparticles. The presence of functional groups is analyzed by FTIR spectroscopy. The UV-visible absorption spectrum of the ZnO nanoparticles shows blue-shift in wavelength corresponding to bulk. The photoluminescence spectrum exhibits a UV emission at 397 nm, a green emission at around 540 nm and a blue emission at 469 nm.